2008
DOI: 10.1128/jvi.01776-07
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Human Papillomavirus Type 16 E6 to E6AP Is Not Required for Activation of hTERT

Abstract: The human papillomavirus (HPV) type 16 (HPV16) E6 protein stimulates transcription of the catalytic subunit of telomerase, hTERT, in epithelial cells. It has been reported that binding to the ubiquitin ligase E6AP is required for this E6 activity, with E6 directing E6AP to the hTERT promoter. We previously reported two E6AP binding-defective HPV16 E6 mutations that induced immortalization of human mammary epithelial cells. Because activation of hTERT is proposed to be necessary for epithelial cell immortalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…1B). This correlates with the prior measurements of lower LQELL peptide interaction affinities with 16E6 in vitro (low micromolar [3]) compared with the affinities of 16E6 for the full-length E6AP in vitro (low nanomolar [21]). …”
supporting
confidence: 71%
“…1B). This correlates with the prior measurements of lower LQELL peptide interaction affinities with 16E6 in vitro (low micromolar [3]) compared with the affinities of 16E6 for the full-length E6AP in vitro (low nanomolar [21]). …”
supporting
confidence: 71%
“…Myc is known to be a direct activator of telomerase in both human keratinocytes and fibroblasts (4,5,28,61), and our previous studies have shown that E6 and Myc physically interact and bind to the hTERT promoter (30,51,58). Indeed, the presence of Myc is required for E6-mediated induction of the hTERT promoter.…”
Section: E6mentioning
confidence: 88%
“…Estrogen, STAT3, and c-Myc have all been shown to activate hTERT (32,34,63). HPV type 16 (HPV16) E6, along with E6-associated protein (E6AP), an E3 ubiquitin ligase, activates transcription of hTERT in epithelial cells (16,23,39), although there has been evidence of E6AP-independent effects by E6 (51). Activation of hTERT by E6-E6AP requires two E boxes found at the hTERT promoter flanking the transcriptional start site (55,58,60).…”
mentioning
confidence: 99%